Food Security Assessment in Kazakhstan - LUKHMANOVA, Gulnar Koishybaevna; SYZDYKBAYEVA, Nurgul Baisharipovna; BAIBULEKOVA, Lyailya Abdybayevna; ABDYKALYK, Samal Ergazykyzy; SEIDAKHMETOVA, Aiym Askarovna (Journal of Advanced Research in Law and Economics; Vol 9 No 4 (2018): JARLE Volume IX Issue 4(34) Summer 2018DO - 10.14505//jarle.v9.4(34).21, 2018)
The article considers the basic aspects of food safety assessment in Kazakhstan. By way of example, the authors describe a set of criterial indicators for assessing the national food security, divided into two groups - strategic and tactical monitoring indicators. Summarizing the theoretical and methodological aspects of food security assessment, the authors propose to expand the list of criteria by adding such indicators as the integrated coefficient of food independence and the complex coefficient of food dependence. According to the authors, such indicators are highly relevant in the CIS countries, since the import expansion in the context of foreign trade liberalization has resulted in displacement of domestic producers from the national market, both in Kazakhstan and in Russia, as well as in Kyrgyzstan and other CIS countries.